Răspuns :
3²⁰¹¹ = 3²⁰¹⁰+1= 3²⁰¹⁰ *3
(3²⁰¹⁰-1) + 3²⁰¹⁰ + (3²⁰¹⁰+1) =3²⁰¹⁰-1+ 3²⁰¹⁰ + 3²⁰¹⁰+1 = 3*3²⁰¹⁰ = 3²⁰¹¹
(3²⁰¹⁰-1) + 3²⁰¹⁰ + (3²⁰¹⁰+1) =3²⁰¹⁰-1+ 3²⁰¹⁰ + 3²⁰¹⁰+1 = 3*3²⁰¹⁰ = 3²⁰¹¹
Deci se observa: 3=0+0+1+0+2
9=2+1+2+2+2+3
etc. =>
=> 3 la 2011=a+a+1+a+2=>
=>3 la 2011 =3×a + 3=>
=>3 la 2011-3= 3 ×a=>
=>3×(3 la 2010-1)= 3×a=>
=>a= 3 la 2010 -1
Daca nu intelegi ceva din ce am scris, sa ma intrebi.
9=2+1+2+2+2+3
etc. =>
=> 3 la 2011=a+a+1+a+2=>
=>3 la 2011 =3×a + 3=>
=>3 la 2011-3= 3 ×a=>
=>3×(3 la 2010-1)= 3×a=>
=>a= 3 la 2010 -1
Daca nu intelegi ceva din ce am scris, sa ma intrebi.